2013
DOI: 10.1210/jc.2013-2912
|View full text |Cite
|
Sign up to set email alerts
|

Iodine Contributes to Thyroid Autoimmunity in Humans by Unmasking a Cryptic Epitope on Thyroglobulin

Abstract: Iodine-induced thyroid autoimmunity is related to TgAb and the unmasking of a cryptic epitope on Tg contributes to this relationship in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 32 publications
5
35
0
1
Order By: Relevance
“…An increased frequency of hypothyroidism has also been reported after the careful introduction of IS in Denmark [14]. Similar findings were reported in the Pescopagano survey, where an increased frequency of TAb and of Hashimoto's thyroiditis (HT) was observed after the beginning of iodine prophylaxis [20]. This study showed that iodine intake modulates the pattern of thyroid diseases, even in case of slight differences in intake and doses below 150 μg daily recommended for preventing IDD.…”
Section: Iodine and Thyroid Diseasesupporting
confidence: 84%
See 2 more Smart Citations
“…An increased frequency of hypothyroidism has also been reported after the careful introduction of IS in Denmark [14]. Similar findings were reported in the Pescopagano survey, where an increased frequency of TAb and of Hashimoto's thyroiditis (HT) was observed after the beginning of iodine prophylaxis [20]. This study showed that iodine intake modulates the pattern of thyroid diseases, even in case of slight differences in intake and doses below 150 μg daily recommended for preventing IDD.…”
Section: Iodine and Thyroid Diseasesupporting
confidence: 84%
“…We have approached this matter in the population of Pescopagano. In a second survey conducted in this village in 2010 [20], 70% of subjects declared to routinely use IS (IS users) and 30% never to use IS (IS non-users). Accordingly, median urinary iodine excretion was slightly higher in IS users than in IS non-users (112.0 vs. 86.5 µg/l; p < 0.01; fig.…”
Section: Iodine and Thyroid Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we searched for recent reports on screening studies of TgAb and TPOAb. To avoid the influence of diseases themselves, we only considered studies done on healthy control subjects in various regions in different countries [24][25][26][27][28][29][30][31][32][33][34][35][36][37]. In healthy subjects, the incidence of positive TgAb or TPOAb is …”
Section: Discussionmentioning
confidence: 99%
“…HT appears to be worsened by iodine intake [46]; in fact, increased levels of thyroid antibodies result after iodine replacement [47]. The proposed mechanism is an increase in thyroglobulin immunogenicity, as a consequence of the presentation of a cryptic pathogenic peptide induced by iodination [48].…”
Section: Iodine Autoimmunity and Cancermentioning
confidence: 99%